RELASI KEKERABATAN BAHASA-BAHASA DI WAKATOBI: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - , SAHUR SAERUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study examines the genetic relation of Wakatobi subgroup languages in Southeast Sulawesi. The languages are spoken in the Wakatobi archipelago in four large cluster of islands that are Wangi Wangi, Kaledupa, Tomia, and Binongko. This study is formulated through synchronic and diachronic viewpoint. Synchronic study includes a description of the phonological system of Wangi- Wangi, Kaledupa, Tomia, and Binongko. Meanwhile diachronic study includes calculation of the level of kinship isolects of Wangi Wangi, Kaledupa, Tomia, and Binongko, investigation on the evidence of separation and unifying of language group in the subgroup of Wakatobi through reconstruction techniques either deductive or inductive reconstruction, as well as investigation on reflex of PAN phonemes and reflex of PAN etymon in the Wakatobi subgroup languages. Diachronic study results with lexicostatistic technique shows the level of kinship Wn-Kd, 70.16%